2022
DOI: 10.1080/08897077.2021.1931634
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Young Women's Alcohol and Cannabis use Linked to Risk for Sexually Transmitted Infection Highlight the Importance of Multi-Level Targeted Interventions: Findings from the Pittsburgh Girls Study

Abstract: Background: Social ecological models designed to understand disparities in sexually transmitted infection (STI) prevalence highlight understudied structural and community risk factors. Guided by a social ecological model, this study identified profiles based on substance use-related STI risk, and examined associations of the profiles with selected indicators of structural-, community-, and individual-level STI risk factors. Methods: Repeated measures latent class analysis was applied to Pittsburgh Girls Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In a study of juvenile justiceinvolved adolescents, researchers found adolescents who were heavy users of both cannabis and alcohol reported more risky sex than those who used only cannabis (Gillman, Yeater, Feldstein Ewing, Kong, & Bryan, 2018). In late-adolescent women, the highest STI risk was among those who used alcohol and cannabis (Chung et al, 2021). Furthermore, in another study, using both cannabis and alcohol at high rates in adolescence was significantly associated with greater likelihood of teen pregnancy, compared to moderate alcohol use (Green et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study of juvenile justiceinvolved adolescents, researchers found adolescents who were heavy users of both cannabis and alcohol reported more risky sex than those who used only cannabis (Gillman, Yeater, Feldstein Ewing, Kong, & Bryan, 2018). In late-adolescent women, the highest STI risk was among those who used alcohol and cannabis (Chung et al, 2021). Furthermore, in another study, using both cannabis and alcohol at high rates in adolescence was significantly associated with greater likelihood of teen pregnancy, compared to moderate alcohol use (Green et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Adolescent substance use is associated with negative consequences, including risky sexual behaviors, which increases the likelihood adolescents experience sexually transmitted infections (STIs) and sexual assault (Chung, Hipwell, Stepp, Miller, & Sartor, 2021;Espelage, Davis, Basile, Rostad, & Leemis, 2018;Green et al, 2017). Although siblings are a main source of social influence during adolescence, few studies have considered how sibling substance use behaviors are related to risky sexual behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of justice-involved adolescents, researchers found adolescents who were heavy users of both cannabis and alcohol reported a higher frequency of unprotected sex than those who used only cannabis (Gillman et al, 2018). In late-adolescent women, the highest STI risk was among those who used alcohol and cannabis (Chung et al, 2021). Furthermore, in another study, using both cannabis and alcohol at high rates in adolescence was significantly associated with greater likelihood of teen pregnancy, compared to moderate alcohol use (Green et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Adolescent substance use is associated with negative consequences, including risky sexual behaviors, which increases the likelihood adolescents experience sexually transmitted infections (STIs) and sexual assault (Chung et al, 2021;Espelage et al, 2018;Green et al, 2017). Although siblings are a main source of social influence during adolescence, few studies have considered how sibling substance use behaviors are related to risky sexual behaviors.…”
Section: Introductionmentioning
confidence: 99%